Linking stakeholder survey, scenario analysis, and simulation modeling to explore the long-term impacts of regional water governance regimes. Issue 48 (April 2015) - Withycombe Keeler, Lauren; Wiek, Arnim; White, Dave D.; Sampson, David A.
Highlights: A multi-method approach is used to construct water governance scenarios of Phoenix, Arizona. Scenarios constructed with normative values and preferences derived from a stakeholder survey. Normative scenarios interface with simulation model to test impacts of values and preferences. Results present four distinct and plausible scenarios of Phoenix in 2030 with impacts to 2080. Water security and sustainability scenarios perform best but require significant intervention. Abstract: Freshwater scarcity is a pivotal challenge for many cities, as resources are threatened by increasing demand, water quality concerns, and climate change impacts. Current governance approaches appear unable to respond effectively to these challenges, prompting calls for transitions to sustainable water governance. Scenarios are often used to explore narrow aspects of water systems, which is not a full realization of their potential to guide transitions in water governance. A transition-oriented approach to scenario construction needs to generate scenarios that (i) are governance focused, including the institutions, actors, and actions that will guide transitions; (ii) are normative, incorporating the values and preferences of those responsible for carrying out transition actions; (iii) are presented as a small set of distinct and identifiable scenarios, which stakeholders can comprehend and compare; and (iv) allow for interfacing with dynamic models to demonstrate the systemic impacts of different approaches to water governance. This research utilizes a participatory, mixed-method approach, including survey, scenario analysis, and simulation modeling to construct distinct, coherent, plausible, and normative governance scenarios of metropolitan Phoenix, Arizona in 2030. Four scenarios provide residents and policy makers with distinct options for future water governance regimes, indicating the future impacts of normative values and preferences that might or might not be aligned with ideas of sustainability.